Mental health and care needs of British children and young people aged 6–17. (July 2021) - Fledderjohann, Jasmine; Erlam, Jayne; Knowles, Bran; Broadhurst, Karen
Abstract: We conducted a scoping literature review based on a sample of 51 UK-based research articles published since 2004, focusing on children and young people aged 6–17 years. Taking the 2004 Office for National Statistics survey of child and adolescent mental health as a pivotal point in the development of the field, our aims were to identify the mental health difficulties featured in extant literature since the survey; uncover critical gaps; and propose avenues for advancing the field. Articles were critically reviewed, coded, and summarised. We found socioeconomic disadvantage, family instability and parental distress are cited as key contributing factors to mental distress. Following categorizations in the 2004 survey, emotional, conduct, and hyperactivity difficulties were the most commonly researched and reported topics. The needs of migrant, BAME, physically disabled, and LGBTQ children were severely underrepresented in the literature, as were those of looked after children. We also found a strong reliance on clinic-based convenience samples, which obfuscates the needs of children who are not able to access care. Further research using inclusive, population-based samples and diverse methods is needed going forward.